Reply to C. Edward Weber - Mandeville, M. J. (Academy of Management Journal, 1961)
Replies to a commentary about the nature of authority in business management. Arguments about the acceptance definition of authority; Discussion on the problem with the lack of a cohesive theory of organization; Importance of authority in an organization.